The need for system modeling of wind power - Lakhoua Najeh; Mohamed Fathi Karoui (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
Nowadays, to further help the environment and to sustain our increasing demand, we need to move to renewable sources of our energy generation. Next, it is necessary to provide simple but powerful description for modeling wind turbine system. Then, we present a system modeling the behavior with sequence diagram and a structural modeling. Finally, we present a modeling with state machine diagram. The aim of this paper is to achieve a functional, structural, and behavior description of a wind turbine using the systems modeling language SysML.